Effects of 13‐Year Nitrogen Additions on Stoichiometric Relationship in the Plant–Soil–Microbial Continuum From Tropical to Boreal Forests - Danhua Zhang; Zhengbin Yan; Di Tian; Suhui Ma; Kai Dong; Chen Yang; Chengjun Ji; Xuemei Yang; Chenhui Chang; Zixuan Wang; Changti Zhao; Jiangling Zhu; et al. (Global Change Biology, 2025)
Ecological stoichiometry in the plant–soil–microbial systems is crucial for regulating nutrient flow and sustaining ecosystem functions in forests. However, how rising atmospheric nitrogen (N) deposition induced by human activities impacts the stoichiometric relationships across ecosystem compartments remains poorly understood. We therefore conducted a 13‐year N‐addition experiment across eight forests from tropical to boreal zones in China, to assess the shifts in carbon:nitrogen:phosphorus (C:N:P) stoichiometry across live plant tissues, detritus, soil, and microbes. The N addition significantly elevated N concentrations in green leaves (+7.2% to 10.1%), twigs (+8.4%), fine roots (+20.2%), and leaf litter (+5.9%), while decreasing microbial N (−16.0%) and P concentrations (−20.2% to − 12.1%) across compartments. These changes triggered compartment‐specific responses, with greater stoichiometric variability in plants than in soils, particularly in high‐latitude forests. However, N addition did not significantly alter the intrinsic scaling relationships of P concentrations and N:P ratios among compartments or the N–P scaling patterns within individual compartments. Our findings provide new insights into the resilience and complexity of nutrient regulation in forests under chronic N deposition, with important implications for predicting long‐term ecosystem responses and developing sustainable nutrient management strategies.